2003
DOI: 10.1002/joc.868
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal modulation of the El Niño–southern oscillation relationship with sea level pressure anomalies over the North Atlantic in October–March 1873–1996

Abstract: The seasonal modulation of the relationship between the sea-level pressure anomalies (SLPAS) over the North Atlantic region (100°W-50°E; 20-70°N) and the sea surface temperature anomalies (SSTAS) in the tropical Pacific (120-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
94
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 35 publications
13
94
1
2
Order By: Relevance
“…Our results suggest that the relationship between ENSO and the North Atlantic atmospheric circulation changes strongly between the beginning and the core-ending parts of the boreal winter. This result is consistent with the mean SLPA (Moron and Gouirand, 2003) and NAO index (Huang et al, 1998) responses to ENSO. This suggests, therefore, that the best seasonal pooling is not DJF, but ND on the one hand and JFM (or FM) on the other hand, when ENSO signals over the North Atlantic area are investigated.…”
Section: Discussionsupporting
confidence: 88%
“…Our results suggest that the relationship between ENSO and the North Atlantic atmospheric circulation changes strongly between the beginning and the core-ending parts of the boreal winter. This result is consistent with the mean SLPA (Moron and Gouirand, 2003) and NAO index (Huang et al, 1998) responses to ENSO. This suggests, therefore, that the best seasonal pooling is not DJF, but ND on the one hand and JFM (or FM) on the other hand, when ENSO signals over the North Atlantic area are investigated.…”
Section: Discussionsupporting
confidence: 88%
“…Though the region of overlap is small, the two indices are positively correlated for the fall season and both are inversely related to the first PC. While it is beyond the scope of this study to explore a physical ENSO-NAO connection, recent research suggests that a link may be present (Moron and Gouirand, 2003). Analysis with additional meteorological data corroborates the large-scale relationships and maintains consistency with established relationships between ENSO and climatological variables such as precipitation and temperature.…”
Section: Summary and Discussionsupporting
confidence: 66%
“…Therefore, with the caution of a still short dataset and the sampling un certainty, we suggest that the use of a longer dataset helps to capture a significant stratospheric signal in strong La Nina winters. In fact, the studies that reported a sur face signal over Europe for La Nina analyzed near 100-yr periods (Moron and Gouirand 2003;Pozo-Vazquez et al 2005).…”
Section: A La Nina Stratospheric Pathwaymentioning
confidence: 99%
“…Concerning the La Nina stratospheric pathway of influence into the troposphere, we recall that a close linkage between La Nina winters and the N AE region has already been found. Negative sea level pressure (SLP) anomalies are observed north of 50°N in late winter during La Nina events (Moron and Gouirand 2003), together with a strong precipitation anomaly pattern over the European region (PozoVazquez et al 2005). This pattern, characterized by en hanced precipitation over Great Britain and Scandinavia and reduced precipitation over the southwestern Medi terranean area, is related to a positive phase of the North Atlantic Oscillation (NAO).…”
Section: Introductionmentioning
confidence: 99%